Synthesis and evaluation of novel aza-aromatics as dual 5-HT2A and 5-HT2C receptor agonists - Adhikari, Amit Singh; Yadav, Annu; Pandit, Soumen; Kumar, Suresh; Pandey, Vinay Kumar; Maurya, Arvind Kumar; Umrao, Deepmala; Chand, Diwan; Maity, Debalina; Gayen, Jiaur R.; Srivastava, Kinshuk Raj; Yadav, Prem N.; et al. (ACS Medicinal Chemistry Letters, 2025)
The 5-HT2A and 5-HT2C receptors are key therapeutic targets for CNS disorders. We investigated whether a nonhallucinogenic dual 5-HT2A/5-HT2C agonist could offer novel treatment potential. Large screening of in-house structurally diverse compounds revealed centhaquin, an FDA-approved hypovolemic shock drug, as a selective 5-HT2C agonist (EC50: 35 nM). We then synthesized 22 aza-aryl analogs with modified piperazine groups, and identified two dual agonists, 3ci and 3dh (EC50 < 1 mu M), with no 5-HT2B activity up to 10 mu M. Molecular docking highlighted critical interactions with Ser159 (5-HT2A) and Ser138 (5-HT2C) on the upper side of the orthosteric binding pocket. Pharmacokinetic studies in mice demonstrated that 3ci was rapidly absorbed in the plasma and brain (T-max = 0.08 h; C-max = 936.4 ng/mL plasma, 2446.8 ng/g brain). Both compounds (3ci and 3dh, 20 mg/kg, i.p.) triggered a head-twitch response but were less potent than the hallucinogenic control 2,5-dimethoxy-4-iodoamphetamine, suggesting a reduced hallucinogenic liability. These results highlight 3ci as a promising lead for developing 5-HT2A/2C dual agonists to treat CNS disorders.
Keywords: 5-HT2A; 5-HT2C; Centhaquin; GPCR; Head Twitch Response; Serotonin Receptor